Pengembangan Model Kurikulum Sekolah Sepakbola (SSB) dengan Pemberian Konsep dan Media Audio Visual - Adi Sucipto; Budijanto Budijanto (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2019)
Football School Curriculum development with giving of concept and audiovisual media aims to improve the quality of football skills. This type of research is the development of research.This study begins with a situation analysis, problem analysis, requirements analysis, design development, validation, limited testing and revision. From the analysis of the situation and the problems found problems being experienced by students Football School caused by factors both internal and external. Football school curriculum needs by providing concepts and audio-visual media, students of need to be given to the Football School. Giving concept before exercise is useful to strengthen memory skills related skills that will be implemented. Learning material that obtained through the medium of vision (visual media), can accelerate absorption learners in understanding literacy classes. The results of the needs analysis shows that Football School curriculum development by the giving concept and audiovisual media very necessary, to improve football skills